2020
DOI: 10.1371/journal.pone.0242302
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the prevalence of common respiratory viruses in children < 2 years with bronchiolitis in the pre-COVID-19 pandemic era

Abstract: Introduction The advent of genome amplification assays has allowed description of new respiratory viruses and to reconsider the role played by certain respiratory viruses in bronchiolitis. This systematic review and meta-analysis was initiated to clarify the prevalence of respiratory viruses in children with bronchiolitis in the pre-COVID-19 pandemic era. Methods We performed an electronic search through Pubmed and Global Index Medicus databases. We included observational studies reporting the detection rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 116 publications
5
47
0
1
Order By: Relevance
“…In children, the virus is linked to rhinitis, acute otitis media, pneumonia, bronchiolitis, and asthma exacerbations ( 97 ). One large meta-analysis showed that HBoV 1 is the third most common viral agent detected in children with bronchiolitis ( 103 ), while other investigators placed HBoV as the third most common virus in children suffering from wheezing with prevalence of 8.1%, following rhinoviruses and respiratory syncytial virus ( 104 ). Due to its non-enveloped nature, HBoV is resistant to disinfectants and detergents, and should be considered as a possible nosocomial pathogen (which is especially pertinent for immunocompromised children) ( 105 ).…”
Section: An Overview and Global Trendsmentioning
confidence: 99%
“…In children, the virus is linked to rhinitis, acute otitis media, pneumonia, bronchiolitis, and asthma exacerbations ( 97 ). One large meta-analysis showed that HBoV 1 is the third most common viral agent detected in children with bronchiolitis ( 103 ), while other investigators placed HBoV as the third most common virus in children suffering from wheezing with prevalence of 8.1%, following rhinoviruses and respiratory syncytial virus ( 104 ). Due to its non-enveloped nature, HBoV is resistant to disinfectants and detergents, and should be considered as a possible nosocomial pathogen (which is especially pertinent for immunocompromised children) ( 105 ).…”
Section: An Overview and Global Trendsmentioning
confidence: 99%
“…The development of molecular diagnostic tests has made it possible to reassess the role of respiratory viruses in bronchiolitis and the description of new viruses [ 11 ]. Systematic reviews have shown that infections with no-HRSV respiratory viruses in childhood are also associated with an increased risk of developing wheezing sequelae [ 18 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in this report, we have only recorded 2 studies with patients > 10 and are therefore unable to comment on the decrease in the strength of the association between LRTI in childhood and the subsequent wheezing risk. The development of molecular diagnostic tests has made it possible to reassess the role of respiratory viruses in bronchiolitis and the description of new viruses [11]. Systematic reviews have shown that infections with no-HRSV respiratory viruses in childhood are also associated with an increased risk of developing wheezing sequelae [18,71].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…6,7 With the development of molecular detection assays, RVs have recently been shown to be also involved in a significant proportion of more severe LRTIs such as wheezing, bronchiolitis, asthma exacerbation and chronic obstructive pulmonary disease. [8][9][10] Rhinoviruses have also been reported in apparently healthy individuals, possibly due to the prolonged viral shedding period. 11,12 Enteroviruses, on the other hand, have a broader tropism and can cause a wide range of human infections including acute respiratory infections, meningitis, encephalitis, gastroenteritis, acute flaccid paralysis or conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%